On the Measurement of Mismatch - Carsten Ochsen (Universität Rostock, Institut für Volkswirtschaftslehre, 2004)
This paper introduces and examines a definition of an equilibrium rate of unemployment that can be used as mismatch indicator, too. In contrast to existing indicators this measurement method is based directly on the Beveridge-Curve. An application of the indicator to nine OECD countries leads to diverging results. Most of the considered countries have experienced increasing mismatch in the seventies and decreasing mismatch in the nineties. The latter result is somewhat surprising, since mismatch was expected to be increasing in the nineties. However, the estimates for Germany are against this international trend, due to the fact that mismatch has increased steadily since the middle of the sixties.
Keywords: J41; J69; E24; 330; Mismatch; Beveridge-Curve; equilibrium unemployment; Beveridge-Kurve; Strukturelle Arbeitslosigkeit; Arbeitslosigkeit; Schätzung; OECD-Staaten; Deutschland; Gleichgewicht